2022
DOI: 10.1021/jacs.2c04037
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Stereospecific Transformations of Alkylboronic Esters

Abstract: Copper-catalyzed stereospecific cross-couplings of boronic esters are reported. Boron “ate” complexes derived from pinacol boronic esters and tert-butyl lithium undergo stereospecific transmetalation to copper cyanide, followed by coupling with alkynyl bromides, allyl halides, propargylic halides, β-haloenones, hydroxylamine esters, and acyl chlorides. Through this simple transformation, commercially available inexpensive compounds can be employed to convert primary and secondary alkylboronic esters to a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Finally, the Morken group has recently reported an example of a regioselective copper-catalyzed protodeboronation of a 1,2-bis(boronate) available through a carbohydrate-catalyzed diboration. 45 The protodeboronation reaction takes place exclusively at the primary boronate, leaving intact the secondary boron atom for a second copper-catalyzed acylation to render a compound that was easily transformed into an anti-HIV analogue of galbulin (Scheme 36).…”
Section: Boronate Allylation Of Carbonylmentioning
confidence: 99%
“…Finally, the Morken group has recently reported an example of a regioselective copper-catalyzed protodeboronation of a 1,2-bis(boronate) available through a carbohydrate-catalyzed diboration. 45 The protodeboronation reaction takes place exclusively at the primary boronate, leaving intact the secondary boron atom for a second copper-catalyzed acylation to render a compound that was easily transformed into an anti-HIV analogue of galbulin (Scheme 36).…”
Section: Boronate Allylation Of Carbonylmentioning
confidence: 99%
“…To engage alkyl electrophiles in Suzuki–Miyaura reactions, palladium, copper, nickel, and iron catalysts have been employed; however, these processes generally require trialkylborane derivatives for productive reaction. While copper catalysis can extend to alkylboronic esters, , until recently, this process was similarly limited to C­(sp 2 ) electrophiles . Recent studies in our laboratory showed that upon activation with t -butyllithium, copper catalysts can facilitate coupling between alkylboronic esters and a range of non-C­(sp 2 ) electrophiles (Scheme c).…”
Section: Introductionmentioning
confidence: 99%
“…While copper catalysis can extend to alkylboronic esters, 7c,d until recently, this process was similarly limited to C(sp 2 ) electrophiles. 10 Recent studies in our laboratory showed that upon activation with t-butyllithium, copper catalysts can facilitate coupling between alkylboronic esters and a range of non-C(sp 2 ) electrophiles (Scheme 1c). Herein, we demonstrate that using simple alkoxide activation, 1,2-bis(boronic esters) exhibit remarkable reactivity in Cu-catalyzed reactions and undergo regioselective coupling with carbon-based electrophiles (Scheme 1d).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Given the widespread availability of alkyne derivatives, the enantioselective construction of a C–C or C–X (X = N, O, etc.) bond at the propargylic position is an especially attractive strategy for accessing versatile chiral building blocks en route to stereochemically and functionally complex targets. , However, in contrast to a variety of well-developed protocols that employ prefunctionalized alkyne derivatives for asymmetric propargylation or metal acetylide precursors for enantioselective nucleophilic addition to synthesize α-chiral alkynes, , the use of simple alkynes for enantioselective propargylic C–H functionalization remains an underdeveloped approach (Scheme A). …”
mentioning
confidence: 99%